Înțelepciunea – cel mai înalt dar al Sfântului Duh pentru omul care se îndumnezeiește - Micevski-Ignat Ilche (Editura Doxologia, Institut für Ökumenische Theologie Ostkirchliche und Patrologie, Universität Graz, 2020)
According to St. Maximus the Confessor, wisdom is the last and highest gift of the Holy Spirit given to man who is on the last step of deification. Man reaches it through the liberation of passions and virtuous life. When man reaches the moment of deification, wisdom reveals many mysteries about the world and God. Wisdom is a door to knowledge of man. In this paper I will endeavor to explain the significance of wisdom for man on the path to deification and his relationship with God, especially on the role of wisdom in knowing God and creation.
Pr. Prof. Dr. Viorel Sava (coord.), Studia Theologica Doctoralia, vol. XII, Aspecte ale cercetării științifice doctorale, astăzi, Editura Doxologia, Iași, 2020
Keywords: gift, wisdom, virtue, deification, grace, knowledge